Antibiotic resistance genes (ARGs) in agricultural soils from the Yangtze River Delta, China - Sun, Jianteng; Jin, Ling; He, Tangtian; Wei, Zi; Liu, Xinyi; Zhu, Lizhong; Li, Xiangdong (The Science of the total environment, 2020)
As an important reservoir of intrinsic antimicrobial resistance, soil is subjected to increasing anthropogenic activities that creates sustained selection pressure for the prevalence of antibiotic resistance genes (ARGs), thus constituting an important environmental dissemination pathway to human exposure. This study investigated the levels and spatial distributions of three classes of ARGs in relation to a range of co-occurring chemical mixtures and soil properties at a regional scale of the Yangtze River Delta (YRD), China. The selected eight ARGs were all detected in 241 agricultural soil samples with relative abundances ranging from 1.01 × 10−7 to 2.31 × 10−1 normalized to the 16S rRNA gene. The sulII and tetG were the dominant ARGs with a mean relative abundance of 6.67 × 10−3 and 5.25 × 10−3, respectively. The ARGs were mainly present in agricultural soils alongside Taihu Lake and Shanghai municipality, the most agriculturally and economically vibrant area of the YRD region. Antibiotics, rather than other co-occurring pollutants and soil properties, remain to be the dominant correlate to the ARGs, suggesting their co-introduction into the soils via irrigation and manure application or the sustained selection pressure of antibiotics from these sources for the proliferation of ARGs in the soils. While the current dataset provided useful information to assess the ARGs pollution for mitigation, future studies are warranted to reveal the complete picture on the potential transfer of antimicrobial resistance from soil to agricultural produces to human consumption and associated health implications. [Display omitted] •Ubiquitous distribution of ARGs at high abundances in regional agricultural soils.•Hotspot areas of ARG pollution concentrated in the most agriculturally vibrant area.•Dominance of antibiotics over co-occurring pollutants and soil properties in ARG prevalence.